Ensuring the Cultural Rights of Kurdish Minority in Türkiye: Necessity, Challenges, Solutions - Fazaeli, Mostafa; Karami, Mousa (The Age of Human Rights Journal, 2023)
Being in non-dominant position and forming one of the largest ethnic groups numerically in Türkiye (previously Turkey), Kurds constitute an ethnic minority. The main argument of this article is that neglecting and disrespecting the cultural rights (CRs) of this group has led to transformation of a social challenge to a political one which ultimately resulted in a security challenge through an armed movement by P.K.K. in the 1980s. Employing a descriptive-analytical method to analyse the content, the present article aims at investigating the necessity of, challenges to and solutions for ensuring CRs of Kurdish minority. It appears that ensuring the cultural rights of Kurdish minority in Türkiye is a pressing necessity particularly for preserving cultural diversity as the common heritage of humanity and maintaining national, regional and international peace and security. Furthermore, the main challenges with which ensuring CRs of Kurds in Türkiye is facing are weak international belief in cultural rights, lack of sufficient national and international monitoring bodies and effective enforcing mechanisms, and dominance of Kemalism as the founding ideology of Republic of Türkiye. Accordingly, the solutions for eliminating these challenges can be strengthening the foundations and developing the sources of cultural rights of ethnic minorities, activating the national and international monitoring bodies and criminalising certain examples of violations of cultural rights and predicting effective sanctions. No article has been written on the necessity of, challenges to and solutions for ensuring the CRs of Kurdish minority in Türkiye in a single piece. Addressing these factors from the perspective of CRs as human rights, this article contributes in filling the existing gap in literature in this regard.